I Don’t Know Why I Want a Māori Midwife, I Just Do! Experiences of One Māori Midwife Who Provides Kaupapa Māori Midwifery Care. - Onekawa, Waimarie (Auckland University of Technology, 2022)
The title of this dissertation “I don’t know why I want a Māori midwife; I just do” sets the tone for this research which aims to understand Māori needs for midwifery care that is embedded in Te Ao Māori values. Midwifery in Aotearoa is largely Eurocentric focusing on the individual woman; however, this study presents whānau and whakawhanaungatanga as central facets. Kaupapa Māori worldviews and research methods have been favoured to celebrate Māori ways of being, knowing, and doing; and to champion Māori philosophies and beliefs. The use of pūrākau as a research tool and a data analysis method has assisted in the alignment of the worldview and has given the freedom to explore meanings with great depth. I have chosen to share my own pūrākau as a Māori woman and a consumer of health, to begin the journey of unravelling the meanings hidden within a lived experience. Further, I have given my account of six journeys from whānau within my midwifery practice and analysed the learnings from my recollection of their journeys. The rich data that resulted helps us develop a broad understanding of Māori experiences of maternity and gives a vision for future research. Some background information is shared that speaks to traditional Māori life and unique cultural characteristics, to help the reader gain insight to what is important and natural for Māori. This information helps inform our nderstanding of current Māori culture, what birth means to Māori, and how we, as health professionals, might provide a better service. The findings confirm that Māori need midwifery care that is built upon Māori worldviews and is whānau centric rather than individually focused. Māori share unique connections with each other through whakawhanaungatanga and whakapapa, and when nurtured within a midwifery relationship can enhance the care provided. For midwifery to progress towards improving experiences and outcomes for Māori, ideas and efforts need to be unified and cooperative. Ultimately, Māori identity begets Māori health. As such, current healthcare systems need to reflect Māori preferred ideologies. The responsibility of improving health for Māori falls on everyone’s shoulders and is not a task left for Māori alone to rectify.